RIM-binding protein links synaptic homeostasis to the stabilization and replenishment of high release probability vesicles. - Muller, M.; Genc, O.; Davis, G.W. (Neuron, 2015)
Here we define activities of RIM-binding protein (RBP) that are essential for baseline neurotransmission and presynaptic homeostatic plasticity. At baseline, rbp mutants have a ~10-fold decrease in the apparent Ca(2+) sensitivity of release that we attribute to (1) impaired presynaptic Ca(2+) influx, (2) looser coupling of vesicles to Ca(2+) influx, and (3) limited access to the readily releasable vesicle pool (RRP). During homeostatic plasticity, RBP is necessary for the potentiation of Ca(2+) influx and the expansion of the RRP. Remarkably, rbp mutants also reveal a rate-limiting stage required for the replenishment of high release probability (p) vesicles following vesicle depletion. This rate slows ~4-fold at baseline and nearly 7-fold during homeostatic signaling in rbp. These effects are independent of altered Ca(2+) influx and RRP size. We propose that RBP stabilizes synaptic efficacy and homeostatic plasticity through coordinated control of presynaptic Ca(2+) influx and the dynamics of a high-p vesicle pool.